Development of Anti-Aging Cream Preparations with Active Substances from Plant Extracts: Physicochemical Review and Potential Applications - Teguh Tanuwidjaja (Jurnal EduHealth, 2023)
Indonesia is known to be rich in biodiversity, including various types of plants that can be used as traditional medicines to treat various skin problems, including acne, skin lightening, and anti-aging. In optimizing efforts to overcome aging caused by free radicals, it is important to develop cosmetic formulations that are effective and comfortable to use. Cosmetics can be in various dosage forms, including gels, creams, powders, ointments, and lotions. It is necessary for the formulation and evaluation of anti-aging cream preparations containing active substances from plant extracts. The method used in this study is comparative research, which involves collecting data from various research journals via the internet. Literature research is conducted online through platforms such as Science Direct, ResearchGate, Google Scholar, and other journal sites. In addition, this study provides information on formulations of anti-aging creams containing active substances from plant extracts based on available scientific evidence in the literature. These findings indicate that the formula used in the development of this cream has the potential to be used in anti-aging products containing active substances from plant extracts. Although the results of this review show success in physicochemical stability, it is important to continue further research to test the effectiveness and safety of using this cream on human skin. More in-depth clinical trials will provide stronger evidence of the benefits and safety of this product. Thus, the development of cream preparations based on the results of this review provides a solid foundation for the development of cosmetic products that combine the natural properties of plants with excellence.